Whose `Special Treatment'? Heterosexism and the Problems with Liberalism - Brickell, Chris (Sexualities, 2001)
This article examines the circulation of heterosexist positions within several recent New Zealand media texts. It argues that a recent form of discourse engages liberal language and assumptions in ways that support the privileged position of heterosexuality and the marginalization of homosexuality. The examples given highlight not only the tenor of some recent representations of homosexuality, but also some problems within liberalism. Most notable of these are liberalism's individualism and its failure to recognize the systemic nature of hierarchical power relationships and the constituting of lesbian and gay subjectivities within these relationships. These problems allow liberalism to play an active part in processes of domination and subordination.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; capitalisme; cours; discipline; discours médiatique; histoire; hétérosexisme; libéralisme; nouvelle-zélande; océanie; premier cycle; périodes historiques; rapports de domination; régions géographiques; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques; violences

Fashioning Sapphism: The origins of a modern English lesbian culture - Doan, Laura L.... (Columbia University Press, 2001)
Le procès pour obscénité très médiatisé de The Well of Loneliness (1928) de Radclyffe Hall est généralement reconnu comme le moment de cristallisation dans la construction d'une culture lesbienne anglaise moderne visible, marquant un grand fossé entre l'innocence et la déviance, le privé et le public, la nouvelle femme et la femme moderne. Lesbienne. Pourtant, malgré un accord sans réserve sur l'importance de ce moment culturel, les études antérieures déforment souvent de manière réductrice notre lecture de la formation de l'identité lesbienne au début du XXe siècle, soit en négligeant d'examiner en détail les développements qui ont conduit à l'interdiction, soit en encadrant les événements dans un cadre trop large. un contexte élargi par rapport à d’autres phénomènes culturels. Fashioning Sapphism situe la romancière Radclyffe Hall et d'autres lesbiennes éminentes, dont la pionnière du maintien de l'ordre des femmes, Mary Allen, l'artiste Gluck et l'écrivaine Bryher, au sein de la modernité anglaise à travers les multiples sites du droit, de la sexologie, de la mode et de la représentation littéraire et visuelle. , retraçant ainsi l'émergence d'une sous-culture lesbienne anglaise moderne au cours des deux premières décennies du XXe siècle. S'appuyant sur de nouvelles recherches approfondies dans les archives, le livre interroge à nouveau une série de mythes longtemps acceptés sans aucun doute (et toujours en circulation) concernant, pour n'en citer que quelques-uns, l'ampleur de l'homophobie dans les années 1920, le déploiement stratégique de la sexologie contre les minorités sexuelles, et la rigidité de certains codes culturels pour désigner le lesbienisme dans la culture publique.
Keywords: 1900-1999; 1910-1919; 1920-1929; approches et analyses; europe; histoire et politique; hétérosexisme; identités LGBTQIA2+; lesbianisme; personnes lesbiennes; périodes historiques; royaume-uni; régions géographiques; sexisme; sexualité; systèmes d'oppressions; thématiques; violences

The Quest for Modern Manhood: Masculine Stereotypes, Peer Culture and the Social Significance of Homophobia - Plummer, David C. (Journal of Adolescence, 2001)
This paper explores the use of homophobic terms by boys and young men and the meanings they invoke when using them. Highly detailed interviews were conducted with young men from diverse backgrounds about their own experiences while growing up and their observations of schools, teachers, family and peers. Homophobia was found to be more than a simple prejudice against homosexuals. Homophobic terms like “poofter” and “faggot” have a rich developmental history and play a central role in adolescent male peer-group dynamics. Homophobic terms come into currency in primary school. When this happens, words like poofter and faggot rarely have sexual connotations. Nevertheless, far from being indiscriminate terms of abuse, these terms tap a complex array of meanings that are precisely mapped in peer cultures, and boys quickly learn to avoid homophobia and to use it decisively and with great impact against others. Significantly, this early, very powerful use of homophobic terms occurs prior to puberty, prior to adult sexual identity and prior to knowing much, if anything, about homosexuality. An effect of this sequence is that early homophobic experiences may well provide a key reference point for comprehending forthcoming adult sexual identity formation (gay or not) because powerful homophobic codes are learned first.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; australie; cours; discipline; homophobie; hétérosexisme; masculinité; nouvelle-zélande; océanie; patriarcat; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques; violences